2016
DOI: 10.4314/bajopas.v8i2.24
|View full text |Cite
|
Sign up to set email alerts
|

Studies of action of heavy metals on caffeine degradation by immobilised <i>Leifsonia sp.</i> strain SIU

Abstract: Caffeine is an important naturally occurring compound that can be degraded by bacteria. Excessive caffeine consumption is known to have some adverse problems. Previously, Leifsonia sp. strain SIU capable of degrading caffeine was isolated from agricultural soil. The bacterium was tested for its ability to degrade caffeine as the sole carbon and nitrogen source. The isolate was encapsulated in gellan gum and its ability to degrade caffeine in the presence of heavy metals was determined. Out of the nine heavy me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Radjendirane et al (1991) showed that mercury can hinder hydroxylases activity like aryl 2,4-dichlorophenol hydroxylase and 3-hydroxybenzoate-6-hydroxylase. Ibrahim et al (2015) found that concentrations of mercury from 0.1 to 1 mg/L affected the degradation of caffeine by Leifsonia sp. isolated from soil.…”
Section: Resultsmentioning
confidence: 99%
“…Radjendirane et al (1991) showed that mercury can hinder hydroxylases activity like aryl 2,4-dichlorophenol hydroxylase and 3-hydroxybenzoate-6-hydroxylase. Ibrahim et al (2015) found that concentrations of mercury from 0.1 to 1 mg/L affected the degradation of caffeine by Leifsonia sp. isolated from soil.…”
Section: Resultsmentioning
confidence: 99%
“…Reports by Radjendirane et al [ 37 ] showed that mercury could hinder hydroxylases activity like aryl 2,4-dichlorophenol hydroxylase and 3-hydroxybenzoate-6-hydroxylase. In another study by Ibrahim et al [ 35 ], the authors found that concentrations of mercury from 0.1 to 1 mg/L affected the degradation of caffeine by Leifsonia sp. isolated from soil.…”
Section: Resultsmentioning
confidence: 99%
“…Molecules 2020, 25, x FOR PEER REVIEW 7 of 13 sites are co-contaminated with organic and metal pollutants. Data from both aerobic and anaerobic systems show that biodegradation of the organic compound may be reduced by metal toxicity [31,[35][36][37]. Widespread use of pesticides and fertilizers may also have led to the presence of heavy metals in soil.…”
Section: Effect Of Mercury (Hg) On the Degradation Of Carbofuran By Immobilized Cells Of Enterobacter Spmentioning
confidence: 99%
“…Mercury toxicity to bioremediation activity can be reduced by the addition of metal immobilising agents (Yusuf et al, 2019). Ibrahim et al (2016) reported that immobilised Leifsonia sp. strain SIU can withstand up to 0.4 ppm Hg in caffeine degradation, helping to reduce Hg toxicity and maintaining the function of the bioremediation agent even in a polluted environment.…”
Section: Effects Of Heavy Metal On Canola Oil Degradationmentioning
confidence: 99%
“…Cd also inhibits the biodegradation of other xenobiotics (Hoffman et al, 2005;Sandrin and Maier, 2003). The inhibitory effect of Cd can be lessened by immobilising the bacteria (Ahmad et al, 2017;Ibrahim et al, 2016). Furthermore, the addition of chemical additives can reduce the toxicity of cadmium ions (El-Deeb and Altalhi, 2009).…”
Section: Effects Of Heavy Metal On Canola Oil Degradationmentioning
confidence: 99%